Mobilized Multipotent Hematopoietic Progenitors Stabilize and Expand Regulatory T Cells to Protect Against Autoimmune Encephalomyelitis - Korniotis, Sarantis; D’Aveni, Maud; Hergalant, Sébastien; Letscher, Hélène; Tejerina, Emmanuel; Gastineau, Pauline; Agbogan, Viviane A.; Gras, Christophe; Fouquet, Guillemette; Rossignol, Julien; Chèvre, Jean-Claude; Cagnard, Nicolas; et al. (Frontiers in Immunology, 2020)
Achieving immunoregulation via in vivo expansion of Foxp3+ regulatory CD4+ T cells (Treg) remains challenging. We have shown that mobilization confers to multipotent hematopoietic progenitors (MPPs) the capacity to enhance Treg proliferation. Transcriptomic analysis of Tregs co-cultured with MPPs revealed enhanced expression of genes stabilizing the suppressive function of Tregs as well as the activation of IL-1β-driven pathways. Adoptive transfer of only 25,000 MPPs effectively reduced the development of experimental autoimmune encephalomyelitis (EAE), a pre-clinical model for multiple sclerosis (MS). Production of the pathogenic cytokines IL-17 and GM-CSF by spinal cord-derived CD4+ T-cells in MPP-protected recipients was reduced while Treg proliferation was enhanced. Treg depletion once protection by MPPs was established, triggered disease relapse to the same level as in EAE mice without MPP injection. The key role of IL-1β was further confirmed in vivo by the lack of protection against EAE in recipients of IL-1β-deficient MPPs. Mobilized MPPs may thus be worth considering for cell therapy of MS either per se or for enrichment of HSC grafts in autologous bone marrow transplantation already implemented in patients with severe refractory multiple sclerosis.